SOCIAL REPRESENTATIONS ABOUT ATHLETES’ TRUST IN THE PERSONALITY OF THE COACH - Vakhnin N.A.; Tatyanina L.G.; Vasiliev D.A.; Mayboroda E.T. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify social perceptions about the trust of athletes in the personality of the coach. Methods and structure of the study. As research methods, a semi-structured interview was used, including free statements of athletes in response to a proposal to list the personality traits of a coach whom they are ready to trust. The scientific work was attended by 105 athletes who are students of universities in St. Petersburg (Lesgaft University, Pushkin Leningrad State University, BSTU "VOENMEH" named after D.F. Ustinov), participating in competitions in the qualification category I - Master of Sports. The study covered 52 gymnasts specializing in rhythmic gymnastics, acrobatics and sports aerobics (38 boys and 14 girls) and 53 combat athletes specializing in boxing, taekwondo, judo, kickboxing (38 boys and 15 girls). Results and conclusions. The social ideas about the trust of athletes to the coach were studied. Comparison of ideas about the trust of athletes-gymnasts and athletes-martial artists to the personality of the coach is carried out. It was revealed that the moral and communicative qualities of a coach, professional competence are paramount for trust in a coach. In the group of athletes specializing in martial arts, it was noted that the strong-willed qualities of a coach are significant.